On the major role played by the lumen curvature of intracranial aneurysms walls in determining their mechanical response, local hemodynamics, and rupture likelihood - Oliveira, I. L. [UNESP]; Cardiff, P.; Baccin, C. E.; Tatit, R. T.; Gasche, J. L. [UNESP] (Elsevier, 2023)
The properties of intracranial aneurysms (IAs) walls are known to be driven by the underlying hemodynamics adjacent to the IA sac. Different pathways exist explaining the connections between hemodynamics and local tissue properties. The emergence of such theories is essential if one wishes to compute the mechanical response of a patient-specific IA wall and predict its rupture. Apart from the hemodynamics and tissue properties, one could assume that the mechanical response also depends on the local morphology, more specifically, the curvature of the luminal surface, with larger values at highly-curved wall portions. Nonetheless, this contradicts observations of IA rupture sites more often found at the dome, where the curvature is lower. This seeming contradiction indicates a complex interaction between the hemodynamics adjacent to the aneurysm wall, its morphology, and mechanical response, which warrants further investigation. This was the main goal of this work. We accomplished this by analyzing the stress and stretch fields in different regions of the wall for a sample of IAs, which have been classified based on particular hemodynamics conditions and lumen curvature. Pulsatile numerical simulations were performed using the one-way fluid-solid interaction strategy implemented in OpenFOAM (solids4foam toolbox). We found that the variable best correlated with regions of high stress and stretch was the lumen curvature. Additionally, our data suggest a connection between the local curvature and particular hemodynamics conditions adjacent to the wall, indicating that the lumen curvature is a property that could be used to assess both mechanical response and hemodynamic conditions, and, moreover, suggest new rupture indicators based on the curvature.
Keywords: Abnormal hemodynamics; Intracranial aneurysms; Lumen curvature; Mechanical response; Numerical simulations; Rupture likelihood